Etika Profesi Advokat dalam Perspektif Hukum Islam - Nur Farah Hana; Mughni Hafilla; Fauziah Lubis (Journal on Education, 2023)
In terms of exercising its profession while being protected by rules, statutes, and codes of ethics, the advocate profession is a reputable one (officium nobile). are not constrained by a biocratic hierarchy and can act independently. Due to this fact, an advocate may occasionally stray from his professional role, which is a violation of the advocate's code of ethics. Ethics is the cornerstone of a profession, so when there are signs of misconduct and disregard for moral principles, there should be a discussion of the code of ethics for the profession of advocates from the standpoint of Islamic law, with the goal of ensuring that advocates carry out their responsibilities in accordance with the established code of ethics and are not too far from Islamic ethics. This writing's methodology is an analytical descriptive research-based form of normative writing. Techniques used in research libraries for data collection that place an emphasis on legal books, journals, articles, and opinions as sources of information when they are pertinent to the issue being studied. The conclusion of this essay is a description of the professional code of ethics for advocates, which incorporates moral ideals that serve as the foundation for an advocate's professional personality and must not violate moral principles and may not hurt the interests of others